The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1071/ah090479
|View full text |Cite
|
Sign up to set email alerts
|

Are immigrants at risk of heart disease in Australia? A systematic review

Abstract: We systematically reviewed the peer-reviewed literature to establish the prevalence of cardiovascular disease (CVD) among immigrants in Australia and whether being an immigrant is a CVD risk factor. Of 23 studies identified, 12 were included. Higher prevalence of CVD was found among Middle Eastern, South Asian and some European immigrants. Higher prevalence of CVD risk factors was found among Middle Eastern and Southern European immigrants. Higher alcohol consumption was found among immigrants from New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Dassanayake et al (2009) studied the prevalence of CVD in immigrant groups in Australia. Their findings suggested that CVD is highest among communities originating in the Middle East and southern European.…”
Section: Cardiovascular Disease In Australiamentioning
confidence: 99%
“…Dassanayake et al (2009) studied the prevalence of CVD in immigrant groups in Australia. Their findings suggested that CVD is highest among communities originating in the Middle East and southern European.…”
Section: Cardiovascular Disease In Australiamentioning
confidence: 99%
“…States (Misra and Ganda, 2007), South Asian communities in Europe (Holmboe-Otteson and Wandel, 2012) and the United Kingdom (Anderson et al, 2005;Bradby 2002a) , and among African (Renzaho,2007) and other migrant communities (Dassanayake et al, 2009) in Australia, most of them showing an increased risk of developing obesity and related conditions post-migration, and are described at greater length below.…”
Section: Approaches To the Study Of Dietary Change In Migrantsmentioning
confidence: 99%
“…The prevalence of NCDs, especially T2DM is often higher among South Asian migrants than among the host population, as well as other migrant communities (Misra & Khurana, 2011). Migrants from South Asian countries such as Pakistan, Bangladesh and India who live in the United Kingdom, Europe, Canada and the United States are identified as being particularly susceptible to obesity-related chronic diseases, particularly T2DM and CHD (Anderson et al, 2005;Bhopal, 2009;Dassanayake et al, 2009;De Maio, 2010;Gilbert & Khokhar, 2008;Harding, 2003;Holmboe-Ottesen & Wandel, 2012;Johansen et al, 2009;Wandel et al, 2008). Their diet has been examined as a possible factor responsible for the increased prevalence of these conditions.…”
Section: The Dynamics Of Migration Food and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] Previous studies have demonstrated that there were differences in prevalence, incidence, occurrence, risk factors and mortality rate of acute coronary syndromes amongst culturally and linguistically diverse (CALD) populations. [38][39][40][41][42][43][44][45][46] Unfortunately, the majority of studies on delay in seeking medical care for chest pain have focused on majority populations who share the same culture, language, and beliefs in the same social and environmental context. 18,22,26,47,48 There are only a few studies which provide evidence in regards to the delay in responding to chest pain among differing ethnic groups, particularly CALD groups.…”
Section: Introduction Backgroundmentioning
confidence: 99%